Robustness of point measurements of carbon dioxide concentration for the inference of ventilation rates in a wintertime classroom - Carolanne V.M. Vouriot; Maarten van Reeuwijk; Henry C. Burridge (Indoor Environments)
Indoor air quality in schools and classrooms is paramount for the health and well-being of pupils and staff. Carbon dioxide sensors offer a cost-effective way to assess and manage ventilation provision. However, often only a single point measurement is available which might not be representative of the CO₂ distribution within the room. A relatively generic UK classroom in wintertime is simulated using Computational Fluid Dynamics. The natural ventilation provision is driven by buoyancy through high- and low-level openings in both an opposite-ended or single-ended configuration, in which only the horizontal location of the high-level vent is modified. CO₂ is modelled as a passive scalar and is shown not to be ‘well-mixed’ within the space. Perhaps surprisingly, the single-ended configuration leads to a ‘more efficient’ ventilation, with lower average CO₂ concentration. Measurements taken near the walls, often the location of CO₂ sensors, are compared with those made throughout the classroom and found to be more representative of the ventilation rate if made above the breathing zone. These findings are robust with respect to ventilation flow rates and to the flow patterns observed, which were tested by varying the effective vent areas and the ratio of the vent areas.